Estimating Value of PT. Sentul City TBK, real Estate Sector Company-Using Four Methods valuation - Mazani, Febrandy; Noveria, Ana (Journal of Business and Management, 2012)
Real Estate sector in Asia, including Indonesia, are experiencing significant progress. This is happens because of the global economic crisis in Europe and America, thus making the investors start to touch the real estate sector, especially Asia. But how big is the value of the real estate sector in Indonesia that makes the investors interested in this sector? From there the author tries to analyze a company engaged in real estate and property sector. PT Sentul City Tbk is a company engaged in the sector and has the most extensive inventory of land in Indonesia compared to other companies in the same sector. In this study, the authors will use four methods to assess the company. The method is Asset-Based Approach, Market Approach, Discounted Cash Flow, and Capitalization Rate. The author also wanted to see whether to assess a company engaged in real estate and property sector will be effective by using the methods already mentioned, especially the Discounted Cash Flow method. The conclusion of this study is that assessing a company engaged in real estate and property sector by using the Discounted Cash Flow method is less effective, especially for companies that have too many land owned.Purpose: Ã‚Â This Ã‚Â research Ã‚Â is Ã‚Â made Ã‚Â to Ã‚Â estimate Ã‚Â the Ã‚Â value Ã‚Â of Ã‚Â PT.Sentul City Tbk. and as the addition, this research also focuses to finding the recommendations that can be implemented to maximize the company value.Design/methodology/approach: The methods that used in this research were Asset Based Approach, Market Approach using P/E Ratio, Discounted Cash Flow using the Weighted Average Cost of Capital as the discount rate, and Capitalization Rate as the adjustment of Net Operating Income to find the value. This research will use the audited fianancial statements from 2007-2011.Findings: The result in this research shows that the company value at the beginning of year 2012 ranged from Rp3,766,066,940,143 - Rp17,153,451,874,388. And the current share price now which is Rp205 per August 10th 2012 is between Rp109-Rp535, which means this company still be a good choice for investors.Research limitations/implications: This research focuses on estimating the value and stock price of the PT. Sentul City Tbk. Originality/value: This paper valuing a public listed company using four method in valuing a firm, and also to know that usingÃ‚Â discounted cash flow to valuing company in company which have high inventory effective or not.Keywords: Valuation; Real Estate Sector; Asset-BasedApproach; Market Approach; Discounted Cash Flow; Capitalization RateCategory: Finance